(untitled) (Journal of Computational Mathematics, 2023)
Graph sparsification is to approximate an arbitrary graph by a sparse graph and is useful in many applications, such as simplification of social networks, least squares problems, and numerical solution of symmetric positive definite linear systems. In this paper, inspired by the well-known sparse signal recovery algorithm called orthogonal matching pursuit (OMP), we introduce a deterministic, greedy edge selection algorithm, which is called the universal greedy approach (UGA) for the graph sparsification problem. For a general spectral sparsification problem, e.g., the positive subset selection problem from a set of m vectors in R^n, we propose a nonnegative UGA algorithm which needs O(mn^2+ n^3/ε^2) time to find a 1+ε/β1-ε/β-spectral sparsifier with positive coefficients with sparsity at most nε^2 ceil, where β is the ratio between the smallest length and largest length of the vectors. The convergence of the nonnegative UGA algorithm is established. For the graph sparsification problem, another UGA algorithm is proposed which can output a 1+O(ε)1-O(ε)-spectral sparsifier with nε^2 ceil edges in O(m+n^2/ε^2) time from a graph with m edges and n vertices under some mild assumptions. This is a linear time algorithm in terms of the number of edges that the community of graph sparsification is looking for. The best result in the literature to the knowledge of the authors is the existence of a deterministic algorithm which is almost linear, i.e. O(m^1+o(1)) for some o(1)=O(((m))^2/3 ^1/3(m)). Finally, extensive experimental results, including applications to graph clustering and least squares regression, show the effectiveness of proposed approaches.